Current strategic development of single-atom electrocatalyst in sensor construction: A mini-review - Mohanraj Jagannathan; Sungbo Cho (Nano Materials Science)
With the development of advanced catalysts, the assessment of emerging single-atom-based electrochemical catalysts (SAECs) has significantly increased owing to their similarity to natural enzymes. They hold substantial potential for the design and construction of electrochemical sensing platforms. The fabrication of single-atom-based electrodes revealed their potential for sensitive and selective analyses. Among various nanomaterials, transition metal element-based single-atom, bimetallic single-atom, and metal-free single-atom, each with well-defined active sites, exhibit enhanced catalytic activity, selectivity, and stability. The rational construction of the composition, size, and the strategic development of single-atom electrocatalysts on carbon platforms to enable them to function effectively in complex environments and demonstrate their efficiency between the active sites and electrode construction strategies. Unlike traditional catalysts, SAECs are considered to potential substitutes for natural enzymes. This perspective has been described in a mini-review that highlights recent developments in transition metal elements-based single/bimetallic single atoms and metal-free single atoms anchored on carbon nanostructures. Additionally, there has been a rise in the fabrication of printed electrodes as sensing platforms for biomedical, environmental, and food toxin detection. The challenges and prospects for SAECs in multiple sensing applications are also concisely elaborated.